Application and Evaluation of the HAL-Q System in Hospital Kitchens - Suwainah Sa-i; Erfun Waehama; Anat Matimu; Arseeyah Lateh; Anat Denyingyhot; Pornpimol Mahamad; Monrudee Khemtham; Warawut Krusung; Kasinee Katelakha (My University, 2023)
After the outbreak of COVID-19, Thailand's public health has gained acceptance by many countries. As a result, more tourists and groups will be willing to travel to access public health services in Thailand. Therefore, there is a need for special foods. Among the types of special foods is Halal food, which complies with Islamic religious principles. Thus, hospital kitchens that meet safety and Halal standards are essential to meet the needs of hospital users, including patients and their relatives. However, a Halal management system in hospital kitchens is required to facilitate Halal food production and ensure quality and safety in terms of physical, chemical, biological, and Halal aspects. This independent study aims to investigate the implementation of the Halal Assurance and Liability Quality system, known as HAL-Q, in hospital kitchens to produce Halal food. This investigation involves a safety analysis consisting of four components: 1) a kitchen readiness assessment; 2) training courses to understand the Halal food production process; 3) on-site consulting to develop a QM manual for hospital kitchens; and 4) audits. Additionally, to verify contamination according to Halal standards, alcohol content and porcine DNA were determined. The results showed no contamination of alcohol and porcine DNA in any of the 20 raw materials used in the Halal kitchen. Chemical hazards were identified in the form of contamination with borax, pesticide residues, and formaldehyde in nine samples. However, the results showed no contamination of chemical hazards in any of the samples tested. Coliform bacteria were examined in 10 samples to monitor microbiological quality; however, no coliform bacteria were found. Furthermore, the results of the personal hygiene assessment of two cooks and employees involved in preparing Halal food indicated that both two cooks and employee passed the assessment for good personal hygiene. In conclusion, this study found that the Halal kitchen analyzed in the hospital has the potential and readiness to provide food services according to Halal standards.
Keywords: Halal products and consumer behavior